2017
DOI: 10.1002/asia.201700369
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Controllability in Alkynylgold(III) Complex‐Based Resistive Memory for Flash‐Type Storage Applications

Abstract: Owing to the demands of state-of-the-art information technologies that are suitable for vast data storage, the necessity for organic memory device (OMD) materials is highlighted. However, OMDs based on metal complexes are limited to several types of transition-metal complex systems containing nitrogen-donor ligands. Herein, attempts are made to introduce novel alkynylgold(III) materials into memory devices with superior performance. In this respect, an alkynyl-containing coumarin gold(III) complex, [(C N H )Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Au-Containing complexes have recently drawn much research attention for application in organic memory devices due to their relatively high chemical stability, environmental benignancy, and favorable photoluminescence properties. 105 For instance, Stoliar et al in 2015 firstly reported a neutral gold dithiolene complex [Au(Et-thiazdt) 2 ] (S1), which behaves as an organic narrow-gap Mott insulator and exhibits a resistive switching as a result of the insulator-tometal transition (IMT) under electric pulses. 106 When electric Scheme 1 Chemical structures of metal-organic complexes (S1-S34) for RRAM.…”
Section: Rram Devices Based On Small-molecule Organometallic Complexesmentioning
confidence: 99%
“…Au-Containing complexes have recently drawn much research attention for application in organic memory devices due to their relatively high chemical stability, environmental benignancy, and favorable photoluminescence properties. 105 For instance, Stoliar et al in 2015 firstly reported a neutral gold dithiolene complex [Au(Et-thiazdt) 2 ] (S1), which behaves as an organic narrow-gap Mott insulator and exhibits a resistive switching as a result of the insulator-tometal transition (IMT) under electric pulses. 106 When electric Scheme 1 Chemical structures of metal-organic complexes (S1-S34) for RRAM.…”
Section: Rram Devices Based On Small-molecule Organometallic Complexesmentioning
confidence: 99%
“…[63] Deprotection of coumarin derivative 4 was the key step in the linear synthesis pathway, because the reaction was only successful using a Olah's reagents (HF-pyridine complex) [64] instead of common reagents like TBAF [65] or K 2 CO 3 . [66] Coumarin derivative 6 was prepared via reaction with AzPTES in the presence of a soluble copper(I) complex. [67] Assembly of silica porous materials and CLSM investigations: It has been shown that the diffusion of penetrants in the pores of IOs is a strongly restricted and rather complex process that depends on the considered length scale.…”
Section: Immobilization Of Fluorescent Coumarin-functionalized Silane In Sio 2 à Io Thin Films and Mesoporous Silicamentioning
confidence: 99%
“…Meanwhile, the growing demand for the search of high‐density electronic memory materials has also led to a surge of attention in charge‐neutral transition metal complexes as the active materials of resistive memories 1 . With the early works on resistive memory devices based on coordination metal complexes, 11,12 there has been a growth of interest in the design of organic and organometallic complexes with rich charge transfer characters for applications in functional resistive memory devices 13–23 …”
Section: Introductionmentioning
confidence: 99%